STUDY OF WORK-LIFE BALANCE AND WELL-BEING AMONG EMPLOYEES FROM THE IT INDUSTRY AND EDUCATION SECTORS - Chandanshive, Ajit Baburao (ShodhKosh: Journal of Visual and Performing Arts, 2022)
This study examines the work-life balance and well-being of employees from the IT and Education sectors, focusing on gender differences and sector-specific challenges. The research explores how work-life balance impacts employee well-being in these distinct sectors and investigates the role of organizational culture, job demands, and personal coping strategies. The study involved 60 employees (30 male and 30 female) from Pune district, with 15 males and 15 females from each sector, all with at least 10 years of experience. Data was collected using the Work-Life Balance Scale (WLBS) and the Ryff Scales of Psychological Well-Being (PWBS). Statistical analysis revealed no significant difference in work-life balance between the IT and Education sectors (t=0.27, not significant) or between male and female employees (t=0.26, not significant). However, employees in the Education sector reported significantly higher well-being compared to their IT industry counterparts (t=2.66, p<0.01). Additionally, female employees reported better well-being than male employees (t=3.919, p<0.001). The study concludes that work-life balance issues are not significantly affected by gender, but sector-related differences in well-being exist, with the Education sector showing higher well-being scores. These findings highlight the importance of understanding sector-specific challenges to enhance employee well-being and work-life balance.